Computational insights into strain-increase allylborations for alkylidenecyclopropanes. Issue 50 (1st June 2022) - Hu, Lingfei; Gao, Han; Hu, Yanlei; Lv, Xiangying; Wu, Yan-Bo; Lu, Gang
Abstract : The reactivity of the strain-increase allylboration with vinylcyclopropyl boronic esters is affected by both the electronic property of the cyclopropyl substituent and the acidity of the boron center. Abstract : The origins of the reactivity of strain-increase allylborations were computationally investigated. The low reactivity of vinylcyclopropyl boronates is due to weak electronic interactions between benzaldehyde and allylboronates. By increasing the acidity of the boron center, the reactivity is significantly improved because the stronger stabilizing O→B interaction effectively compensates for destabilizing steric effects.